Keratosis follicularis spinulosa decalvans. - Selvaag, E. (European Journal of Pediatric Dermatology, 2018)
We present a patient with keratosis follicularis spinulosa decalvans (KFSD), suffering from cicatricial diffuse alopecia of the scalp, ulerythema ophryogenes of the eyebrows and cheeks, generalized keratosis pilaris and corneal opacities. Histological investigations showed fibrosis of the scalp, leading to destruction of follicles. Scanning electron microscopical investigations of affected hair showed deformation of the hair shaft. These findings are not pathognomonic for keratosis follicularis spinulosa decalvans, but represent the abnormal growth when hair follicles are destroyed. KFSD belongs to a group of disorders characterized by follicular hyperkeratosis and scarring. It is most likely transmitted by X-linked dominant inheritance.